2019
DOI: 10.1021/acs.langmuir.9b03086
|View full text |Cite
|
Sign up to set email alerts
|

Does Sucrose Change Its Mechanism of Stabilization of Lipid Bilayers during Desiccation? Influences of Hydration and Concentration

Abstract: Sugar–membrane interactions are believed to be responsible for cell preservation during desiccation and freezing, but the molecular mechanism by which they achieve this is still not well understood. The associated decrease of the main phase transition temperature of phospholipid bilayers is explained by two opposing views on the matter: the direct sugar–phospholipid interaction at the bilayer interface (water replacement hypothesis) and an entropy-driven phase transition with sugar molecules concentrating away… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 71 publications
12
38
0
Order By: Relevance
“…Thus, the sugar distribution near the membrane surface at high sugar concentration becomes heterogeneous, which is proposed in the literature. 12,16,21 Note that, for C > 0.4 M, sugar molecules in the intermembrane solution interact with the membrane surface covered with sugar molecules, so this surface may possess different attractive/repulsive properties as compared with the pure lipid surface.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the sugar distribution near the membrane surface at high sugar concentration becomes heterogeneous, which is proposed in the literature. 12,16,21 Note that, for C > 0.4 M, sugar molecules in the intermembrane solution interact with the membrane surface covered with sugar molecules, so this surface may possess different attractive/repulsive properties as compared with the pure lipid surface.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Also, it has been proposed that membrane–sugar interactions may be attractive at low sugar concentrations and repulsive at high concentrations . The importance of both attractive and repulsive membrane−sugar interactions was discussed in a number of publications. , …”
Section: Introductionmentioning
confidence: 99%
“…It was shown that at temperatures high enough to cause thermal disruption, structural damage to the bilayer is prevented to a significant extent by the interaction of sugar molecules with the phospholipid head groups [119]. Recent MD simulations of the interaction of sucrose with DOPC bilayers at different levels of hydration have shown that sugar molecules interact preferentially with the lipid bilayer interface as described above at low concentration and/or high hydration, but at high concentration or low hydration they preferentially accumulate in the inter-bilayer solution as the bilayer interface becomes saturated with sugar molecules [121].…”
Section: Common Quantities In Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Interactions in the sugar membrane are postulated to be responsible for preserving cell integrity during dehydration and freezing. According to Stachura et al (2019), the water replacement hypothesis occurred where the sucrose molecules interact with the bilayer phospholipid headgroups at low sucrose concentrations with high water content. These interactions and the network of hydrogen bonds with water molecules reinforce the stability of proteins and membrane bilayer during dehydration.…”
Section: Discussionmentioning
confidence: 99%